Central African Economic and Monetary Community (CEMAC) : Staff Report on the Common Policies in Support of Member Countries Reform Programs. (IMF Staff Country Reports; Country Report ;, 2017)
This paper examines common policies supporting reform programs in member countries of the Central African Economic and Monetary Community. The sharp decline in oil prices has profoundly impaired the region's external and fiscal balances. Oil export proceeds and budget oil revenues have plummeted between 2014 and 2016. Several measures have been taken or are planned by the Bank of Central African States (BEAC) to support countries' adjustment programs and help re-build reserves. BEAC has started to tighten the monetary policy stance with a first increase in its policy rate. The BEAC will also gradually eliminate its statutory advances to member countries, and will ensure implementation of strict limits aimed at restricting bank refinancing using government securities as collateral.